Real-world experience with the pentaspline pulsed field ablation system: one-year outcomes of the FARADISE registry - Boersma, Lucas V A; Széplaki, Gábor; Dello Russo, Antonio; García-Bolao, Ignacio; Efremidis, Michael; Szegedi, Nándor; Willems, Stephan; Haqqani, Haris; Gandjbakhch, Estelle; Solimene, Francesco; Andrikopoulos, George; Fiala, Martin; et al. (Europace, 2025)
AIMS: Clinical studies with protocol-mandated workflow and monitoring have analysed performance of pulsed field ablation (PFA) for treating atrial fibrillation (AF). The FARADISE registry captures global use of the pentaspline PFA catheter in real-world clinical practice with a follow-up of 3 years. METHODS AND RESULTS: FARADISE is a prospective, non-randomized, multi-national registry (NCT05501873) that enrolled subjects clinically indicated for ablation using the pentaspline PFA catheter per medical judgement and hospital standard-of-care. Procedural characteristics, safety, and clinical effectiveness up to 12-months were collected. In total, 1158 AF patients received PFA across 48 centres in 21 countries (64 ± 11 years, 33% female, 90% de novo, 65% paroxysmal AF). Pulmonary vein isolation (PVI)-only procedures were performed in 80.8% of paroxysmal vs. 57.5% for non-paroxysmal patients (P < 0.01). Median procedure, left atrial dwell, and fluoroscopy times were 51[40-70], 31[24-41], and 12[8-17] min, respectively. The rate of early onset serious adverse events was 1.5% and did not differ by ablation strategy or AF indication. At 1-year, clinical effectiveness was 80.8% for paroxysmal AF and 67.7% for non-paroxysmal AF, with no difference within indication by lesion set (paroxysmal: 81.2% PVI-only vs. 79.0% PVI+, P = 0.65; non-paroxysmal: 67.5% PVI-only vs. 67.7% PVI+, P = 0.79). Acute results reinforce a short procedural learning curve with no difference in 1-year effectiveness by operator experience. CONCLUSION: The FARADISE registry provides a snapshot of real-world clinical use of the pentaspline PFA catheter. Acute results demonstrate favourable procedural and safety outcomes regardless of AF indication. One-year outcomes are encouraging, with no differences seen within indication based on ablation strategy.
Keywords: výsledek terapie; Recurrence; Learning curve; Male; Equipment Design; Aged; Prospective Studies; mužské pohlaví; senioři; registrace; Catheter Ablation; recidiva; design vybavení; Real-world; Atrial Fibrillation; Pulmonary Veins; Time Factors; Treatment Outcome; lidé; Cardiac Catheters; ženské pohlaví; Pulsed field ablation; Humans; časové faktory; venae pulmonales; Atrial fibrillation; Registries; katetrizační ablace; Female; lidé středního věku; srdeční katétry; fibrilace síní; Middle Aged; prospektivní studie